Analyzing Use of “Thanks to You”: Insights for Language Teaching and Assessment in Second and Foreign Language Contexts - Lanteigne, Betty; Crompton, Peter (Research in Language, 2011)
This investigation of thanks to you in British and American usage was precipitated by a situation at an American university, in which a native Arabic speaker said thanks to you in isolation, making his intended meaning unclear. The study analyzes use of thanks to you in the Corpus of Contemporary American English and the British National Corpus to gain insights for English language instruction /assessment in the American context, as well as English-as-a-lingua-franca contexts where the majority of speakers are not native speakers of English or are speakers of different varieties of English but where American or British English are for educational purposes the standard varieties. Analysis of the two corpora revealed three functions for thanks to you common to British and American usage: expressing gratitude, communicating “because of you” positively, and communicating “because of you” negatively (as in sarcasm). A fourth use of thanks to you, thanking journalists/guests for being on news programs/talk shows, occurred in the American corpus only. Analysis indicates that felicitous use of thanks to you for each of these meanings depends on the presence of a range of factors, both linguistic and material, in the context of utterance.